Tungsten Carbide Processing and Applications - Liu, Kui (IntechOpen, 2012)
Tungsten Carbide - Processing and Applications, provides fundamental and practical information of tungsten carbide from powder processing to machining technologies for industry to explore more potential applications. Tungsten carbide has attracted great interest to both engineers and academics for the sake of its excellent properties such as hard and wear-resistance, high melting point and chemically inert. It has been applied in numerous important industries including aerospace, oil and gas, automotive, semiconductor and marine as mining and cutting tools, mould and die, wear parts, etc., which also has a promising future particularly due to enabling to resist high temperature and are extremely hard.